Conquering the world in leaps and bounds: hopping locomotion in toads is actually bounding. (28th March 2015) - Reilly, Stephen M.; Montuelle, Stephane J.; Schmidt, Andre; Naylor, Emily; Jorgensen, Michael E.; Halsey, Lewis G.; Essner, Richard L.
Summary: While most frogs maximize jump distance as an escape behaviour, toads have traded jump distance for endurance with a strategy of hopping repeatedly. This strategy has enabled toads to expand across the continents as one of the most diverse groups of anurans. Multiple studies have revealed physiological endurance adaptations for sustained hopping in toads, however, the kinematics of their sequential hopping behaviour, per se, has not been studied. We compared kinematics and forces of single hops and multiple hopping sequences and quantified field performance of hopping behaviours in free ranging toads of three species and discovered a novel aspect of locomotion adaptation that adds another facet to their exceptional terrestrial locomotor abilities. We found that bouts of repeated hopping are actually a series of bounding strides where toads rotate on their hands and then land on their extended their feet and jump again without stopping. In addition, free‐ranging toads appear to use bounding locomotion more frequently than single hops. Bounding in toads has the advantage of maintaining velocity and producing longer jump distances. In comparison to single hops, cyclic bounding steps reduce energy expenditure and appear to provide limb loading dynamics better suited for potential cycling of elastic energy from stride to stride than would be possible with repeated single hops. This is the first case of the common use of a bounding gait outside of mammals. Bounding adds a key terrestrial locomotor trait to the toad's phenotype that may help explain their history of global expansion and the challenges to modern faunas as introduced toads rapidly invade new ecosystems today. Abstract : Lay Summary